Could alluvial knickpoint retreat rather than fire drive the loss of alluvial wet monsoon forest, tropical northern Australia?. Issue 11 (6th April 2016) - Larsen, Annegret; May, Jan‐Hendrik; Moss, Patrick; Hacker, Jorg
Abstract: Drainage rejuvenation through headward migration of alluvial knickpoints is common in ephemeral semi‐arid streams, but has not yet been described for tropical rivers. In the Australian monsoon tropics (AMT), wet monsoon forests have an important ecological function, and are present along many alluvial valleys and springs within a eucalypt‐savanna dominated landscape. Using a combination of LiDAR, remote sensing and field evidence, we observe the ongoing destruction of wet monsoon forest through hydro‐geomorphic feedbacks, along with the headward retreat of an alluvial knickpoint at Wangi Creek in Litchfield National Park, Northern Territory. Due to the highly transmissive shallow aquifer along the lower Wangi Creek, this knickpoint retreat leads to a downstream drop in in‐channel water level, which in turn drives a decrease in the local groundwater table. The lowered groundwater level causes the shallow anabranches and formerly water saturated peaty floodplain soil to desiccate, which results in a reduction of vegetation density. The resulting dry surface conditions allow annual to bi‐annual high frequency low‐intensity fires to affect the monsoon forest, while wet rainforest upstream of the knickpoint remains intact. In this paper, we argue that such hydro‐geomorphic feedbacks may cause the initial destabilization of the forest, which then provides the necessary conditions for the impact of fire. This scenario thus challenges the prevalent view that fire is a first‐order control on the spatial extent of wet monsoonal rainforest in the study area, and provides a new and testable hypothesis for further studies in the AMT. Copyright © 2016 John Wiley & Sons, Ltd.